Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A Double-blind, Randomized, Placebo-controlled Crossover Study Evaluating Reducose® Mulberry Leaf Extract at 3 Levels Shows Significant Effects on Postprandial Blood Glucose and Insulin After Eating a Complex Meal - B. Davis; P. Thondre; J. Tammam; I. Butler; M. Lane; A. Gallagher (Journal of the Academy of Nutrition and Dietetics, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Trait-based approach reveals how marginal reefs respond to acute and chronic disturbance - B. Sommer; I. R. Butler; J. M. Pandolfi (Coral Reefs, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Last Glacial pollen–climate reconstructions from Northland, New Zealand - R.M. Newnham; B. V. Alloway; K.A. Holt; K. Butler; A.B.H. Rees; J.M. Wilmshurst; G. Dunbar; I. Hajdas (Journal of Quaternary Science, 2017)
Despite wide‐ranging interest in the vegetation and climate of Northland, New Zealand, during the last glacial cycle, the region and timeframe lack quantitative climate reconstructions while land‐based pollen records have tended to be poorly dated and fragmentary. The region is also important for geochronology due to the co‐occurrence of the Rotoehu tephra, a widely dispersed isochron near the current limits of radiocarbon dating, and extensive subfossil wood remains of Agathis australis , with strong dendrochronological and dendroclimatological potential. We present new pollen records and temperature reconstructions from three sites set in coastal dune belts from western mid‐Northland (∼35°S), all containing Rotoehu tephra, that collectively span the last 70 ka. The phases and amplitude of temperature changes broadly align with those reported from elsewhere in New Zealand and with marine isotope climate–stratigraphic records, including maximum temperature depression of 6–8 °C during the last glacial maximum. We argue that these climatic patterns are intimately linked to shifts in the southern westerly wind belt, the northern margins of which extend to the region today. Correspondence between the Northland temperature shifts and atmospheric CO 2 supports the model of ocean–atmosphere CO 2 flux modulated by latitudinal migration of the southern westerlies. Copyright © 2017 John Wiley & Sons, Ltd.

Displacement Forecasting Method in Brittle Crack Surrounding Rock Under Excavation Unloading Incorporating Opening Deformation - X. J. Li; W. M. Yang; L. G. Wang; I. B. Butler (Rock Mechanics and Rock Engineering, 2014)

The impacts of flooding on the high-latitude, terrigenoclastic influenced coral reefs of Hervey Bay, Queensland, Australia - I. R. Butler; B. Sommer; M. Zann; J.-x. Zhao; J. M. Pandolfi (Coral Reefs, 2013)

Precious metal enrichment in the Platreef, Bushveld Complex, South Africa: evidence from homogenized magmatic sulfide melt inclusions - D. A. Holwell; I. McDonald; I. B. Butler (Contributions to Mineralogy and Petrology, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Hyperglycemic oxoaldehyde, glyoxal, causes barrier dysfunction, cytoskeletal alterations, and inhibition of angiogenesis in vascular endothelial cells: aminoguanidine protection - Sean M. Sliman; Timothy D. Eubank; Sainath R. Kotha; M. Lakshmi Kuppusamy; Shariq I. Sherwani; Elizabeth Susan O’Connor Butler; Periannan Kuppusamy; Sashwati Roy; Clay B. Marsh; David M. Stern; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2010)

Redox-active antioxidant modulation of lipid signaling in vascular endothelial cells: vitamin C induces activation of phospholipase D through phospholipase A2, lipoxygenase, and cyclooxygenase - Emily Steinhour; Shariq I. Sherwani; Jessica N. Mazerik; Valorie Ciapala; Elizabeth O’Connor Butler; Jason P. Cruff; Ulysses Magalang; Sampath Parthasarathy; Chandan K. Sen; Clay B. Marsh; Periannan Kuppusamy; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2008)

Some properties of adenylate kinase from chemolithotrophically grown Thiobacillus novellus - I. R. C. McKellar; A. M. Charles; B. J. Butler (Archives of Microbiology, 1980)